Automatic Integration of IoT Devices - Pêgo, Pedro Ruben Januário (2017)
During the last years a new concept has gained prominence in the technology world. With an increasingly dominant role in our days, Internet of Things (IoT) is a technological revolution that is changing our lives. The imagination is the limit for the new devices that may appear in the market. This phenomenon is derived from both, the technological evolution and the growing acceptance of this type of products in our social life. Faced with a fast growth, an increasing diversity and with the existing uncertainty about the new devices emerging in the market, there is a need to integrate each new device in our lives. However, nowadays, there is no existing structure prepared for the actual diversity in IoT world. Applications that integrate devices from many different vendors are now available, but these rely on manual configuration by the application developers for every new device integrated, which is tedious and requires application updates to be rolled out frequently. An application that can discover the new device properties, and decide to which class of devices it belongs to can automatically generate an interface and the necessary integration drivers for the new device with no/less human intervention. This is the main direction of this works’ contribution. To achieve this goal we need to identify the device that is communicating inside a network using the information shared by IoT devices. The final results show that IoT communication data can be used to identify the device, mainly if in possession of a considerable sized device information database.